Identification of Factors Influencing Donor-Derived Cell-Free DNA Levels up to One Year After Kidney Transplant - Ahmad Mirza; Imran Gani; Imran Parvez; Cari Weaver; Laura Mulloy; Rajan Kapoor (Journal of Transplantation)
Conclusion: This study provides further insight into donor and recipient variables’ effects on dd-cfDNA in the early posttransplant phase by analyzing a more diverse cohort of patients and adds to the knowledge around interpreting dd-cfDNA scores with clinical correlation for posttransplant management.